Dynamics of a Market Share Model for Enterprises with Coopetition Strategy. (26th November 2013) - Zhao, Mingxia
Abstract : A deterministic model is used to study the change of the market share with coopetition strategy for enterprises. The model takes into consideration both coopetition enterprises and other enterprises, and the coopetition threshold R 0 is identified and global dynamics are completely determined by R 0 . It shows that R 0 is a global threshold parameter in the sense that if R 0 < 1, the coopetition free equilibrium is globally stable and the market share of coopetition enterprises tends to zero, whereas if R 0 > 1, there is a unique coopetition equilibrium which is globally attractive with some conditions, and thus the market share of coopetition enterprises tends to a steady state value. By some sensitivity analysis of R 0 on parameters, we conclude that the size of the coopetition threshold R 0 and coopetition equilibrium depended on the cooperation competitiveness of coopetition enterprises.